GEN Z AT WORK: EXPLORING FACTORS SHAPING ORGANIZATIONAL CITIZENSHIP IN THE TOURISM WORKFORCE - Rasyid, Muhammad Farhan (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
The Covid-19 pandemic caused the tourism industry to a drastic degression, in 2022 the tourism industry will bounce back because foreign tourists will return to Indonesia. To accelerate the economic growth of the tourism industry, it is necessary to improve services from employees working in the tourism sector. This can be done with support from the company and also work autonomy, so that Gen Z employees can adapt services to conditions in the field. This research aims to identify the Perceived Organizational Support (POS) and Autonomy of Work with the mediation of Self-efficacy (SE) and Sense of Personal Control can influence Organizational Citizenship Behavior (OCB). This research sample consists of generation Z frontline employees in the Tourism Industry. This research using quantitative methods with 411 respondents. This research using Structural Equation Model, LISREL tools to analyze mediating effects. The results of this research identify that Perceived Organizational Support, Autonomy of Work, Self-efficacy and Sense of Personal Control have a significant positive influence on Organizational Citizenship Behavior.